Pembuatan Peta Desain Tapak KUPS Wisata KTH HKm Sukkuru Mappoji - H Harmudinsyah; Akbar Fuad Husain (Universitas Hasanuddin, 2022)
Padang Loang, Botto Lai, is one of the areas in the Coppo Village which contains a Community Forest area called Sukkuru Mappoji. Within the forest area, there are areas that have not been developed and have the potential to become tourist KUPS. The location has the potential for waterfall tourism and a stretch of nature with a view of the City of Barru. Members of the Sukkuru Mappoji HKm Farmers Group do not yet have a site plan map that can be used as a guide in realizing the